Turmeric and Its Pharmacological Properties- A Review - RAM V, VAMSHI; S, DR. PREETHA. (The journal of contemporary issues in business and government, 2021)
Turmeric is a flowering plant, Curcuma longa of the ginger family, Zingiberaceae, the roots of which are used in cooking. The plant is a perennial, rhizomatous, herbaceous plant local to the Indian subcontinent and Southeast Asia, that calls for temperatures between 20 and 30 °C (68 and 86 °F) and a large amount of annual rainfall to thrive. Plants are gathered each year for their rhizomes, a few for propagation in the following season and some for consumption. This is a review based study on topic turmeric over viral diseases, articles based on turmeric were referred completely which were taken from “pub med”, “google scholar”, PMC. Around 20-25 articles were referred. Other articles which have done a study on medicinal and pharmacological properties of turmeric are also compared. Hence turmeric has a wide range of biological activities which can be used for preparation of various formulations for the treatment of various conditions.